Biosociocultural dan Pilihan Berobat pada Masyarakat Nelayan di Kelurahan Pasia Nan Tigo Kota Padang - Sri Meiyenti; Syahrizal Syahrizal (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
Biosociocultural concept in health anthropology study is use to understand health and illness in society. This study aimed to describe the biosociocultural of fishing communities regarding the concept of health and illness and to identify and describe treatment methods in fishing communities related to the biosociocultural concept. This study used a qualitative method. Data was collected by observation and in-depth interviews. The findings were the healthy concept defined if there was no pain, feeling unwell, strong energy, good appetite, feeling happy, not stressed, no disturbance from supernatural beings and smooth income. On the other hand, it hurted if there was an unpleasant feeling such as dizziness, nausea, vomiting, and body aches so that it interfered with daily activities. If the people getting sick, then the treatment for the pain their suffer was done in several ways. In the early stages, they self-medicate with concoctions from plants they knew or over-the-counter medicines in the stalls. Furthermore, if the illness is considered serious, then it is taken to a healer according to the cause of the disease. If the disease was considered to be caused by social and cultural factors by supernatural beings, it would be taken for treatment to a shaman. Then, if the disease was caused by biological aspects such as the night wind, cold weather or rain, as well as because of food, then they sought treatment at modern health facilities.